Correlation of Physical Activity, Family Income and Consumption of Fruits and Vegetables with the Incidence of Obesity in Adolescents - Firdausi Ramadhani; Franning Deisi Badu; Lisa Djafar; Sunarti Hanapi; Dwi Tama Pahrun (UNIB Press, 2021)
Obesity is defined as an increase in energy intake compared to expenditure, resulting in depletion of body fat and eventually wearing weight. The prevalence of obesity has increased sharply in the Asia Pacific region. Many factors cause obesity. Based on data obtained from the Gorontalo District Health Office in 2018, it shows that the incidence of obesity was 8.795 cases (30.9%) consisting of 1.971 men (6.9%) and 6.824 women (24.0%). Objective: To determine several factors related to the incidence of obesity in adolescents in several high schools in Gorontalo District. This type of research uses observational analytic with a cross sectional study design. The population in this study were all students of class X and XI in SMA Negeri 1 Telaga and SMA Negeri 1 Tibawa, Gorontalo Regency as many as 1.341 students. By using the sampling technique of Proportional Stratified Random Sampling as many as 171 samples. With data analysis techniques using thetest Chi Square. The results of the study of physical activity and consumption of fruits and vegetables had no relationship with the incidence of obesity in adolescents in several high schools in Gorontalo District. Meanwhile, family income has a relationship with the incidence of obesity in adolescents in several high schools in Gorontalo Regency in 2019. It is hoped that each school can increase various activities that can reduce obesity problems and can also provide education in the form of health education to students.